Domestic Petroleum Product Prices and Subsidies : Recent Developments and Reform Strategies - Coady, David; Baig, Taimur; Mati, Amine; Ntamatungiro, Joseph (Washington, D.C. : International Monetary Fund, 2007)
The paper reviews recent developments in the pass-through of international to domestic petroleum product prices, in the different fuel pricing regimes, and in fuel subsidies in a range of emerging market and developing economies. The main finding of the paper is the limited price pass-through in many countries and the consequent increase in fuel subsidies. The paper proposes that key elements of a successful strategy to contain subsidies should comprise: making subsidies explicit; making pricing mechanisms more robust; combining reductions in subsidies with measures to protect the poorest; using the resulting savings well, and transparency and consultation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet